2013
DOI: 10.1590/s0100-55022013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Tele-educação e monitoria ativa no ensino da saúde bucal a estudantes de medicina

Abstract: Verificar o nível de conhecimento basal de alunos do quinto ano de Medicina sobre saúde bucal e mensurar os ganhos em conhecime nto e a habilidade de aconselhamento após treinamento.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The quality of the service of tele-education and tele-assistance has been proved by different authors (Eskenazi, Martins, & Ferreira, 2013;Hersh, Junium, Mailhot, & Tidmarsh, 2001;Rafiq & Merrell, 2005;Roine, Ohinmaa, & Hailey, 2001;Shaikh, Lehmann, Kaleida, & Cohen, 2008;Vucković et al, 2003); however, the cost-effectiveness relation still deserves investigation (Soirefmann, Blom, Leopoldo, & Cestari, 2008).…”
Section: Overview Of Distance Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the service of tele-education and tele-assistance has been proved by different authors (Eskenazi, Martins, & Ferreira, 2013;Hersh, Junium, Mailhot, & Tidmarsh, 2001;Rafiq & Merrell, 2005;Roine, Ohinmaa, & Hailey, 2001;Shaikh, Lehmann, Kaleida, & Cohen, 2008;Vucković et al, 2003); however, the cost-effectiveness relation still deserves investigation (Soirefmann, Blom, Leopoldo, & Cestari, 2008).…”
Section: Overview Of Distance Learningmentioning
confidence: 99%
“…The authors observed the performance of distance learning students was superior to the performance of on-campus students and concluded that the course on medical informatics was successfully implemented by means of distance learning technologies, had a favorable satisfaction from students, and demonstrated learning. Eskenazi, Martins, and Ferreira (2013) aimed at verifying the increase in knowledge and the counseling skills of students in the fifth year of a graduate course in medicine regarding the practice of oral health after a course of interactive tele-education. The study assessed 148 students that were divided into four groups (a control group and three others) that received progressive face to face and distance learning interventions.…”
Section: Overview Of Distance Learningmentioning
confidence: 99%
“…Essas atividades certificam o monitor curricularmente e o qualificam para uma possível carreira docente. Além desses intentos, a literatura apresenta diversas vantagens de uma disciplina ter um monitor, pois ele traz uma narrativa nova na relação docente-discente, é de uma geração aproximadamente dos alunos cursistas, e se identifica (monitor-alunos cursistas) na linguagem, no comportamento, na semiótica, nos saberes tecnológicos, nas relações sociais virtuais, e na possível dificuldade com o aprendizado do conteúdo (HAAG et al 2008;ESKENAZI;MARTINS;FERREIRA JUNIOR, 2013;GARCIA;SILVA FILHO;SILVA, 2013; DANTAS, 2014;SANTOS et al 2015;FRISON, 2016). O monitor ao longo do percurso da monitoria precisa tomar posse dos saberes docentes para aplicar e refletir sobre a teoria (techné), a práxis e a poesia (poiesis) da pratica educativa (FREIRE, 2002).…”
unclassified